Cultural and economic barriers and opportunities for the participation of women in agricultural production systems: a case study in Guatemala - Hernandez, Manuel A.; Alarcon, Constanza; Berrospi, Maria Lucia; Lopera, Diana; Quintero, Diana; Reyes, Byron; Olivet, Francisco (Frontiers in Sustainable Food Systems, 2023)
As in other Latin American countries, agricultural activities in Guatemala contribute with 32% of the total employment (65% in rural areas), but only one in every ten individuals employed in these activities are women. This study examines the cultural and economic barriers and opportunities for the participation of women in agricultural (crop and livestock) production systems. We rely on a qualitative approach involving focus group discussions with 15-20 women in each of the eight communities visited in the departments of Chiquimula (Dry Corridor) and Huehuetenango (Western Highlands) in October 2022. The study provides several interesting findings, which generally hold across locations. First, women do not seem to have a strong preference for crop production activities, except harvesting, and only get involved in specifically assigned tasks. This lack of interest and participation in crop-related activities, which can be related to low empowerment levels and traditional stereotypes in the community about gender roles, persist even in locations with a higher emigration of men, where women could be expected to take over traditionally male crop-related tasks. Second, participants carry out a variety of other unpaid activities, including raising small-scale livestock and maintaining home gardens, which they do not recognize as formal, income-generating occupations despite their more active role. Third, women consider the commercialization of their products a persistent challenge as they do not have access to markets beyond their community, which additionally results in a deterrent to applying for credits due to a generalized fear of defaulting. Despite their day-to-day economic hardship, participants’ main aspirations point to generating more income in non-crop-related activities, mainly livestock farming and raising, or, alternatively, emigrating to provide a better future for their children. These findings remark the importance of offering extensive support to women to not only start new activities, as it has been the case of several public and private initiatives in the area, but help them through continuous extension services on production, storage, and commercialization; management and accounting; and financial literacy, as well as on building agency capacity through existing women groups and organizations and enabling the environment for improved access to markets and credit.